2020
DOI: 10.1177/0021998320948125
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness-toughness balance in PP/EPDM/SiO2 ternary blend-nanocomposites: The role of microstructural evolution

Abstract: The effect of microstructural evolution with hydrophilic-nanosilica (SiO2) concentration, ranging from 0 to 5 wt%, on mechanical properties and deformation micromechanisms of PP/EPDM/SiO2 (80/20/x) ternary blend-nanocomposites was investigated. Morphological observations revealed that, SiO2 nanoparticles tend to localize either around the dispersed EPDM particles or at the PP/EPDM interface, promoting the formation of three dimentional network-like EPDM/SiO2 composite structures dispersed in the PP matrix, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Some of these studies have been composite-based ones in which copolymers or blends of PP with rubbery polymers have been developed and produced with different fillers. 1,2 The required hardness/strength of PP has been recovered and its drawing performance improves when PP/elastomer blends are used together with the fillers. In ternary nanocomposite systems containing elastomer and nanoclay, there is a clear relationship between the location/distribution of the nanoclay and the shape of the elastomer particles, and the morphology and mechanical properties of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have been composite-based ones in which copolymers or blends of PP with rubbery polymers have been developed and produced with different fillers. 1,2 The required hardness/strength of PP has been recovered and its drawing performance improves when PP/elastomer blends are used together with the fillers. In ternary nanocomposite systems containing elastomer and nanoclay, there is a clear relationship between the location/distribution of the nanoclay and the shape of the elastomer particles, and the morphology and mechanical properties of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some documents indicated that as a nucleating agent, the introduction of nanoparticles into PPR will cause heterogeneous nucleation of the matrix, which leads to an increase in crystallization temperature. 12,46 In this study, the Tc of PZ increased by 1 C when the nano-fillers were 8 phr. This phenomenon shows that heterogenous nucleation, which needs a higher temperature, was occurred in PZ.…”
Section: Crystallization Behaviorsmentioning
confidence: 55%
“…Then, they were cooled to 0 C at a rate of 10 C min −1 , held about 5 min at current temperature, and reheated to 190 C at a heating rate of 10 C min −1 . The crystallinity of PPR (Xc) in the samples was estimated from the second heating cycle using the following equation: 12 Xc…”
Section: Analysis Of Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] Despite unique properties provided by EPDM rubber phase, it reduces PP stiffness. For dealing with this drawback, the recent studies have shown that rigid nanofillers, such as nanosilica, [26,27] nanoclay (NC), [28,29] carbon black (CB), [30,31] carbon nanotubes (CNT), [32,33] graphene, [34,35] etc., can greatly increase mechanical properties of blends.…”
Section: Introductionmentioning
confidence: 99%